Sile (Pencak Silat Nias) as a Negotiation of Religion and Culture between Traditional Societies, Islam, and Christianity in Ono Niha - Waruwu, Famati; Tambunan, Elia; Harefa, Otieli; Gulo, Nestilina; Apvan Bertin Baene, Ria (Jurnal Sosiologi Agama, 2024)
Pencak  Silat  is  no  longer  limited  to  martial  arts  but  goes  far  beyond  this.  Suppose  it  is  generally  understood  as  a  martial  art  commonly  called  Sile.  In  that  case,  it  needs  to  be  seen from the socio-theological praxis of the people of Moro’ö District, West Nias Regency, and the people of Tugala Oyo District, North Nias Regency, where they are Nias people in general  who  tend  to  believe  traditionally  based  on  customs,    as  well  as  Christian  church  congregations,  including  Muslims.  This  article  delves  into  Nias’  traditional  pencak  silat  in  2022-2023.  The  empirical  problem  in  Christianity  is  that  there  is  a  tendency  to  label  synchronicity  that  pencak  silat  as  a  traditional  rite  for  primitive  people,  has  always  been  associated with an attempt to display the dimension of “evil spirits” as opposed to the “good spirits”  in  the  Christian  faith  with  the  modern  eyes  of  urban  people.  Meanwhile,  Muslims  tend to be positioned as immigrants. This paper is in the social setting of North and West Nias as a research field, and it is carried out with empirical qualitative research with a socio-theological approach. Data were collected by observation, interview, and documentation. It was found that there is an increasing immersion in cultural arts expressed through pencak silat as a social space (medium) for people of different faiths and traditions. It was found that North and West Nias Sile displayed spatial negotiations between culture and religion.